Penyesuaian Diri Mahasiswa Bercadar Di Universitas Malikussaleh - Syarwinda Syarwinda (Jurnal Psikologi Terapan, 2020)
This study aims to examine in depth about how the adjustment that occurs in veiled students at Malikussaleh University. This study uses qualitative research with phenomenological methods. The selection of research subjects used a purposive sampling technique of 5 people, with criteria, namely only using veils of approximately 1 year and under, and aged 18-25 years. Data collection methods use in-depth interviews and observations so that the supporting instruments in the form of interview and observation guidelines. Data analysis techniques using analysis techniques according to Fereday & Muir-Cochrane, by means of analysis and then interpreting the findings in the field. The results of this study indicate that, the subject undergoes a process of self-adjustment, namely the phase of internal and external motivation, emotions / feelings, learning process and self-actualization. The aspects of adjustment that are experienced also include 3 aspects, namely: insight, life purpose, and the term of self-defense. Then the obstacles that affect the adjustment, namely: social / cultural support such as support from parents and friends. But the most influential is social media.